Respuesta :
We can answer this question by solving each equation for one variable, and then substituting.
3x + y = 11 Given
y = -3x + 11 Subtract 3x from both sides
This equation is now solved for y. Now, let's do the other equation. Make sure to solve it for the same variable.
-2x + y = 1 Given
y = 2x + 1 Add 2x to both sides
Now, let's set both equations equal to each other, since they both equal y.
2x + 1 = -3x + 11 Set both equations equal to each other
1 = -5x + 11 Subtract 2x from both sides
-10 = -5x Subtract 11 from both sides
2 = x Divide both sides by -5
Now, let's substitute x in for one of the equations we found earlier, so that we can find y.
y = 2x + 1 Given
y = (2)(2) + 1 Substitute the x-value, 2
y = 4 + 1 Multiply
y = 5 Add
So, x = 2 and y = 5.
Hope this helps!
3x + y = 11 Given
y = -3x + 11 Subtract 3x from both sides
This equation is now solved for y. Now, let's do the other equation. Make sure to solve it for the same variable.
-2x + y = 1 Given
y = 2x + 1 Add 2x to both sides
Now, let's set both equations equal to each other, since they both equal y.
2x + 1 = -3x + 11 Set both equations equal to each other
1 = -5x + 11 Subtract 2x from both sides
-10 = -5x Subtract 11 from both sides
2 = x Divide both sides by -5
Now, let's substitute x in for one of the equations we found earlier, so that we can find y.
y = 2x + 1 Given
y = (2)(2) + 1 Substitute the x-value, 2
y = 4 + 1 Multiply
y = 5 Add
So, x = 2 and y = 5.
Hope this helps!
First will make Equation take on the form of y = mx + b. I've cchosen the second Equation:
y = 2x + 1
Now substitute this equation in for y into the other equation and solve:
3x+y = 11
3x+ (2x + 1)=11
5x + 1 = 11
5x = 11 - 1
5x/5= 10/5
x = 2
You can now plug this x-value back into either equation, and solve for y:
y = 2(x) + 1
y = 2(2) + 1
y = 5
y = 2x + 1
Now substitute this equation in for y into the other equation and solve:
3x+y = 11
3x+ (2x + 1)=11
5x + 1 = 11
5x = 11 - 1
5x/5= 10/5
x = 2
You can now plug this x-value back into either equation, and solve for y:
y = 2(x) + 1
y = 2(2) + 1
y = 5